State of empowerment : low-income families and the new welfare state - Barnes, Carolyn, 1987- (University of Michigan Press, 2020)
"On weekday afternoons, dismissal bells ring at thousands of schools across the country. These bells signal not just the end of the school day but also the beginning of another important enriching activity: federally funded after-school programs offering tutoring, homework help, and basic supervision. After-school care reflects major shifts in social policy towards social services that support youth development and help low-income parents maintain employment. The scope of after-school programs has grown significantly in the last two decades- nearly one in four low-income families enroll a child in an after-school program. Beyond sharpening students' math and reading skills, these programs also teach important lessons to parents. In a remarkable turn of events-especially given the long history of social policies that leave recipients feeling policed, distrusted, and alienated-government funded after-school programs have quietly become powerful forces for political and civic engagement. Using ethnographic accounts of three organizations, Carolyn Barnes reveals how interactions with government funded after-school programs can enhance the civic and political lives of low-income citizens"--